2001
DOI: 10.1289/ehp.01109533
|View full text |Cite
|
Sign up to set email alerts
|

Work characteristics and pesticide exposures among migrant agricultural families: a community-based research approach.

Abstract: There are few data on pesticide exposures of migrant Latino farmworker children, and access to this vulnerable population is often difficult. In this paper we describe a community-based approach to implement culturally appropriate research methods with a migrant Latino farmworker community in Oregon. Assessments were conducted in 96 farmworker homes and 24 grower homes in two agricultural communities in Oregon. Measurements included surveys of pesticide use and work protection practices and analyses of home-du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(73 citation statements)
references
References 7 publications
1
69
2
1
Order By: Relevance
“…However, we only visited the homes at 6 month intervals and therefore do not have information about usage patterns during other seasons. Residential exposure to agricultural pesticides has been previously documented for families of agricultural workers (Simcox et al, 1995;Fenske et al, 2000;Lu et al, 2000;McCauley et al, 2001). The majority of families in this Rio Grande community did not work on farms, but merely lived in community adjacent to farm fields.…”
Section: Discussionmentioning
confidence: 81%
“…However, we only visited the homes at 6 month intervals and therefore do not have information about usage patterns during other seasons. Residential exposure to agricultural pesticides has been previously documented for families of agricultural workers (Simcox et al, 1995;Fenske et al, 2000;Lu et al, 2000;McCauley et al, 2001). The majority of families in this Rio Grande community did not work on farms, but merely lived in community adjacent to farm fields.…”
Section: Discussionmentioning
confidence: 81%
“…Recent studies have examined in detail the exposure and uptake of pesticides in children who reside in agricultural communities ( Loewenherz et al, 1997;Fenske et al, 2000;Lu et al, 2000;O'Rourke et al, 2000;Sumner and Langley, 2000;McCauley et al, 2001 ). One of the findings of these studies is that children who live in agricultural communities had five times higher pesticide metabolites in their urine than children who resided in nonagricultural communities .…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the take-home pathway to household contamination may also be dependent on the number of people bringing the pesticides from the fields. In Oregon, the concentration of azinphos methyl in house dust was correlated with the number of farmworkers living in the house (McCauley et al 2001). The composition of the household may also be a factor.…”
Section: Environmental Media and Personal Exposure Measurementsmentioning
confidence: 99%
“…During the sample collection period for these studies, chlorpyrifos and diazinon were still allowed for residential purposes and the large variability observed in reference homes most likely indicates indoor applications. Furthermore, concentration of pesticides in dust from farmworker homes was associated with household pesticide use in California and Washington , Bradman et al 1997 but not in Oregon (McCauley et al 2001, McCauley et al 2003. Several studies have demonstrated that proximity to fields where pesticides are applied is related to pesticide levels in house dust , McCauley et al 2001).…”
Section: Environmental Media and Personal Exposure Measurementsmentioning
confidence: 99%
See 1 more Smart Citation